2008
DOI: 10.1021/la802714v
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Se@Ag2Se Core−Shell Colloids and Nanowires into Trigonal Se Nanorods and Uniform Spherical Ag2Se Colloids

Abstract: Physical separation of Ag(2)Se colloids and trigonal (t) Se nanowires transformed from amorphous (a) Se@Ag(2)Se core-shell spherical colloids and from t-Se@Ag(2)Se core-shell nanowires was conducted above the softening temperature ( approximately 132 degrees C) of Ag(2)Se. The Ag(2)Se shells in a-Se@Ag(2)Se core-shell colloids were first collapsed and then transformed into isolated solid spheres as the a-Se cores were dissolved in solvent and transformed into separate t-Se nanowires. In t-Se@Ag(2)Se core-shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Coinage metal chalcogenides (Ag 2 E, Cu 2 – x E, where E = S, Se) have been synthesized using hot-injection chemistries typical of quantum dot formation with uniform sizes but do not typically give rise to the formation of anisotropic shapes. For example, Brutchey et al have demonstrated the use of solvent systems such as ionic liquids and thiol–amine mixtures to create metal chalcogenide nanocrystalline products. Cation and anion exchange have also been used successfully to produce chalcogenide and pnictide nanocrystals. In the work of Vela et al, the silylative deoxygenation of metal oxides with trimethylsilyl reagents has produced several different nanophases, including heterobimetallic structures . The choice of both metal salt anions and metal–ligand coordination chemistry has been demonstrated to have a profound effect on crystal morphology and surface structures.…”
Section: Introductionmentioning
confidence: 99%
“…Coinage metal chalcogenides (Ag 2 E, Cu 2 – x E, where E = S, Se) have been synthesized using hot-injection chemistries typical of quantum dot formation with uniform sizes but do not typically give rise to the formation of anisotropic shapes. For example, Brutchey et al have demonstrated the use of solvent systems such as ionic liquids and thiol–amine mixtures to create metal chalcogenide nanocrystalline products. Cation and anion exchange have also been used successfully to produce chalcogenide and pnictide nanocrystals. In the work of Vela et al, the silylative deoxygenation of metal oxides with trimethylsilyl reagents has produced several different nanophases, including heterobimetallic structures . The choice of both metal salt anions and metal–ligand coordination chemistry has been demonstrated to have a profound effect on crystal morphology and surface structures.…”
Section: Introductionmentioning
confidence: 99%
“…Diethyldithiocarbamato tellurium(IV) and [(CH 3 ) 4 N] 4 Ge 4 Se 10 have also been used as single source precursors for the formation of tellurium with flower-like morphology and selenium nanowires by Wang et al and Gautam et al, respectively. However, it is desirable to develop more simple routes for the synthesis of Se and Te of diverse morphologies from the same single source precursors under different experimental conditions, which could improve the performance of the existing devices and also act as a good template for the preparation of important functional materials, such as Cu 2 Se, Ag 2 Se, Bi 2 Se 3 , CdSe, CdTe, PbTe, and Nb 3 Te 4 . …”
Section: Introductionmentioning
confidence: 99%